The effect of Averrhoa Carambola L. on hemoglobin, blood pressure, defecation, and IL-6 serum levels - Isna Hudaya; Muliatul Jannah (Poltekkes Kemenkes Yogyakarta, 2019)
Prevention of anemia by consuming Fe tablets causes many complaints such as nausea, vomiting, constipation. The majority of WHO countries (132 to 159) have health problems particularly anemia among women and children. To address this issue and minimize its side effect, needed an alternative such as Averrhoa Carambola L (ACL) fruit which also contains iron. This fruit contains several compounds like flavonoid, alkaloid, saponin, protein, fat, calcium, phosphorus, iron/Fe, and vitamin A, B1 and C. Antioxidant content within this fruit is oxalic acid. In addition, the high nutrients in this fruit function as a dietary supplement. This investigation examined the effect of ACL on Hemoglobin (Hb), Blood Pressure (BP), defecation and IL-6 serum levels. This study explored literature reviews on ACL and its effect on Hb, BP, defecation, and IL-6. Keywords used in this study were of ACL, hemoglobin concentration, blood pressure, defecation, IL-6 serum concentration, health, anemia, hypertension, obstipation, immunity, mechanism, and evidence. Based on literature analysis, it showed that ACL improved Hb level, decreased BP, prevent obstipation, and lowered IL-6 serum. ACL can be given to women and children in Indonesia, but it needs further investigation to determine the appropriate dosage will be prescribed.